Complete Heart Block and Persistent Lactic Acidosis as an Initial Presentation of Non-Hodgkin Lymphoma in a Critically Ill Newly Diagnosed AIDS Patient. (6th November 2014) - Ijaz, Mohsin; Tariq, Hassan; Niazi, Masooma; Lvovsky, Dmitry
Abstract : A 66-year-old male with newly diagnosed untreated acquired immunodeficiency syndrome (AIDS) presented with chronic nonspecific complaints of weakness, fatigue, myalgia, and weight loss. His initial EKG showed complete heart block necessitating temporary pacemaker placement. He had no previous history of cardiac disease. He was also found to have a persistent lactic acidosis and imaging studies showed abdominal lymphadenopathy. The patient underwent biopsy of these lymph nodes and was found to have diffuse large B-cell lymphoma. The hospital course was complicated by respiratory failure requiring mechanical ventilator support and cardiac arrest. Patient remained critically ill; he was not a candidate for chemotherapy and, after a month of hospitalization, he died. Lactic acidosis and heart block as an initial presentation of non-Hodgkin lymphoma in an AIDS patient are an unusual and unique presentation.